Analytical modeling of a desiccant wheel - Lee, Dae-Young; Kim, Dong-Seon (ELSEVIER SCI LTD, 2014)
A simple integral model is presented for a desiccant wheel. The original governing equations for a desiccant wheel were simplified to a set of linear ordinary differential equations and an analytical solution was obtained. A brief analysis is given about the solution regarding the non-dimensional numbers that decide the behavior of a desiccant wheel. From the solution, algebraic expressions were obtained for time-averaged heat and mass transfer rates and the results were compared with a numerical model and a set of experimental data in the literature. In comparison with the numerical model, relative error was found less than 12% at 120 degrees C regeneration temperature and 10% standard deviation was observed with the experimental data. The analytical model is considered capable of describing a symmetric desiccant wheel realistically. (C) 2014 Elsevier Ltd and IIR. All rights reserved.
Keywords: NONLINEAR ANALOGY METHOD; MASS-TRANSFER; HYGROSCOPIC WHEELS; DESIGN THEORY; ROTARY HEAT; PERFORMANCE; PREDICTION; EXCHANGERS; BEHAVIOR; AIR